2018
DOI: 10.3389/fpls.2018.00377
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Gene Expression Disturbance by Single A1/C1 Chromosome Substitution in Brassica rapa Restituted From Natural B. napus

Abstract: Alien chromosome substitution (CS) lines are treated as vital germplasms for breeding and genetic mapping. Previously, a whole set of nine Brassica rapa-oleracea monosonic alien addition lines (MAALs, C1-C9) was established in the background of natural B. napus genotype “Oro,” after the restituted B. rapa (RBR) for Oro was realized. Herein, a monosomic substitution line with one alien C1 chromosome (Cs1) in the RBR complement was selected in the progenies of MAAL C1 and RBR, by the PCR amplification of specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…This observation has also been noted in other species, where an uneven distribution of RGAs on chromosomes appears to be common in plants (Kohler et al ., ; Meyers et al ., ; Porter et al ., ; Yang et al ., ; Zhou et al ., ). This uneven distribution might be due to recent tandem gene amplifications, segmental duplications (Rice Chromosomes 11 and 12 Sequencing Consortia, ) and dosage compensation (Zhu et al ., ). Gene dosage balance is critical for development and phenotypic characteristics, especially in synthetic B. napus individuals at initial generations (Xiong et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…This observation has also been noted in other species, where an uneven distribution of RGAs on chromosomes appears to be common in plants (Kohler et al ., ; Meyers et al ., ; Porter et al ., ; Yang et al ., ; Zhou et al ., ). This uneven distribution might be due to recent tandem gene amplifications, segmental duplications (Rice Chromosomes 11 and 12 Sequencing Consortia, ) and dosage compensation (Zhu et al ., ). Gene dosage balance is critical for development and phenotypic characteristics, especially in synthetic B. napus individuals at initial generations (Xiong et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The advent of high-throughput sequencing technologies has facilitated the analysis of genome-wide gene expressions involving aneuploids. Recently, numerous studies demonstrated that dysregulated genes in aneuploidy are not only restricted to altered chromosome but also disomic chromosomes (Huettel et al, 2008; Makarevitch and Harris, 2010; Letourneau et al, 2014; Zhu et al, 2015, 2018; Zhang et al, 2017), suggesting that this dysregulation in gene expression may be a collective transcriptional response to aneuploidy (Sheltzer et al, 2012). Phenotypic consequences in aneuploidy might result from cis -effects or trans -effects or global alterations of the entire regulatory system (Prestel et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers initially believed that phenotypic consequences of aneuploidy are mainly influenced by gene dosage effects of altered chromosomes, which is supported by the correlation between chromosome copy numbers and relative gene expression levels in Down syndrome (Mao et al, 2003), aneuploid yeast (Torres et al, 2008), as well as various types of cancer cells (Gao et al, 2007; Xu et al, 2010; Lu et al, 2011). However, studies on aneuploids in Drosophila and plants showed that changes in the gene expression levels were observed along altered copy numbers ( cis -effects) as well as in unaltered disomic chromosomes ( trans -effects) (Guo and Birchler, 1994; Birchler and Veitia, 2007; Huettel et al, 2008; Malone et al, 2012; Zhu et al, 2015, 2018; Zhang et al, 2017; Rey et al, 2018). In addition, the phenotypic consequences of aneuploidy are believed to result from either the contribution of altered dosages or the impact of a genome imbalance involving the rest of the genome (Guo and Birchler, 1994; Birchler and Veitia, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, aberrant segregation events during mitosis or meiosis can result in aneuploidy, a condition in which cells acquire a karyotype that is not a whole-number multiple of the haploid complement. The balance between chromosome types and the genes they encode is disturbed, resulting in the altered expression of many genes [15].…”
Section: Introductionmentioning
confidence: 99%
“…As described in detail previously [13], the availability of intraspecific aneuploids (including hypoploids such as nullisomics and monosomics, as well as hyperploids such as trisomics and tetrasomics) and interspecific aneuploids (harboring alien chromosome additions or substitutions) has greatly contributed to studies of chromosome homoeology, genomic analysis, and the chromosomal localization of genes [14–20]. However, it is challenging to produce hypoploid s in Brassica and few have been reported [4, 5, 2123]. Nulli-tetrasomics are individuals in which one chromosome pair is missing but four copies of another nonhomologous chromosome are present.…”
Section: Introductionmentioning
confidence: 99%